Semi-quantitative risk assessment of peste des petits ruminants introduction with wild animals into Russian Federation - S. V. Shcherbinin; F. I. Korennoy; T. P. Akimova; A. K. Karaulov (Ветеринария сегодня)
The Russian Federation was officially recognized free from peste des petitts ruminants (PPR). As far as the disease infects both domestic and wild small ruminants, it is important to identify the level of the threat associated with the wild fauna diversity in the neighboring countries, where PPR outbreaks were reported. For that reason, habitats of various disease susceptible animal species were examined. Habitats of the wild susceptible animals were mapped for further examination of the interactions between different animal species using zoological research data; PPR outbreaks in wild animals were also designated in the map thus allowing for the detection of the potential routes of the infection spread in the population and introduction to the country. Analysis of the PPR epidemic situation in the country demonstrated that the disease cases were reported in wild mountain animals (ibices and moufflons) and migratory steppe animals (gazelles and saigas). Risk of this highly contagious viral disease spread in wild small ruminants in Mongolia was reported (probability 0.77). Expert survey was carried out for the determination of possible trends and factors of the infection introduction with the wild susceptible animals, through which small ruminant epizootologists assessed the risk probability. During the survey it was determined that PPR was expected to be introduced from Mongolia (probability 0.81), and of major significance were seasonal migrations of wild animal populations. The resulted semi-quantitative parameters of the potential risk can be recommended for the arrangement and implementation of measures aimed at prevention of PPR introduction and spread in the intact domestic and wild small ruminant populations inhabiting the territory of the Russian Federation.